2017
DOI: 10.1108/gm-01-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of organizational innovation: a framework

Abstract: Purpose This study aims to examine the effect of gender perspectives in organizational leadership and culture on organizational innovations within the oil and gas industry in the United Arab Emirates (UAE). Design/methodology/approach The study examined research in the area of organizational innovation and proposed a framework to help practitioners to create an environment that promotes and strengthens innovation thinking at an institutional level. Findings Based on the literature, a framework of organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
(53 reference statements)
1
23
0
2
Order By: Relevance
“…They suggested strategies for better knowledge management for each type of innovation in the main Brazilian business sectors. A study on the oil and gas industry in the UAE by Busaibe et al (2017) revealed that a diverse management team improves the interactions between the employees and their leaders. It encourages innovation in order to address competition.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…They suggested strategies for better knowledge management for each type of innovation in the main Brazilian business sectors. A study on the oil and gas industry in the UAE by Busaibe et al (2017) revealed that a diverse management team improves the interactions between the employees and their leaders. It encourages innovation in order to address competition.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The idea presented by these women participants suggests that innovation is recognized as an important factor in order to be competitive (Abdul Rahman et al 2015; Busaibe et al, 2017). In addition, the women participants in this study view innovation as important for new product development.…”
Section: Invention Of New Ideasdeveloping New Productsmentioning
confidence: 76%
“…It may be the case that not only is the adoption of DMP more likely among firms with more diverse boards; the implementation of these practices, for example, by human resource professionals, may be more effective. One would expect that firms with more diverse corporate boards should be more likely to have cultures that are more supportive of diversity since BD is related to corporate culture (Busaibe, Singh, Ahmad, & Gaur, 2017). Support for diversity from top management should also be higher since corporate boards influence top management teams (e.g., Williams, Fadil, & Armstrong, 2005).…”
Section: Implications For Human Resources Managementmentioning
confidence: 99%